THE CHALLENGE OF HYBRID LEARNING IN TEACHING ENGLISH FOR BUSINESS - Restu Januarty Hamid; Nurdin Noni; La Sunra (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study explores the implementation and challenges of hybrid learning in English for Business courses at a higher education institution. With the increasing integration of online and face-to-face learning modalities, hybrid education offers opportunities for flexible learning environments but also presents significant obstacles. The research employs a qualitative methodology, involving semi-structured interviews, classroom observations, and document analysis, to gather insights from four lecturers who specialize in Business English education. Findings indicate that technological barriers, including poor internet connectivity and low digital literacy, particularly in remote areas, pose major challenges. Additionally, fostering student interaction and engagement in the online components of hybrid courses is difficult due to platform limitations and passive participation. Lecturers employ strategies such as group tasks and interactive quizzes to enhance engagement, but face-to-face interaction remains critical for developing communication skills. The study also reveals that students struggle with information management skills in the online context, and despite lecturer interventions, they require continuous support to improve their research abilities. Moreover, educators face challenges in balancing the needs of online and in-person students and adapting traditional assessment methods to the hybrid model. The study highlights the importance of training, institutional support, and strategic planning in overcoming these challenges and optimizing hybrid learning for business education